Beliefs of Municipal School Principals About Teacher Commitment [Creencias de Directores de Establecimientos Educacionales Municipales Acerca del Compromiso Docente] - Pasmanik-Volochinsky, D (Universidad Austral de Chile, 2021)
This study is part of research targeted to the advancement in the understanding of teachers and principals’ leadership relationship as elements linked to education improvement, focused specifically on teachers’ commitment. It enquires, by means of a qualitative approach, school principals’ beliefs concerning this commitment. Results show that commitment is understood as a professional attribute, a way of valuing teaching’s role, expressed as an extraordinary devotion to students, learning and school. There also emerge beliefs about teaching, teachers and the municipal system as components of a beliefs system. Beliefs show an idealized teachers’ commitment, contrasting with beliefs concerning teachers, characterized by a strong negative accent. Therefore, a discrepancy is generated with eventual consequences for leadership practices that justify farther investigation. © 2021